An Empirical Analysis of Significant Factors influencing Entrepreneurial Behavior in the Information Technology Industry - Kasanagottu, Suresh; Bhattachar, Sudipto; ., . (International Journal of Engineering and Technology, 2018)
The purpose of the current empirical research paper is to study and comprehend the significant factors that influence the entrepreneurial behavior through a detailed survey among the key employees of the information technology (IT) industry. The data thus collected from the survey was examined through the method of Partial Least Squares (PLS) for evaluating the relationship among the constructs of the conceptual research model. The results of the current empirical research study reveal that entrepreneurship-institutional linkage has the strongest effect on entrepreneurial behavior, followed by role of outsourcing and nature of the industry. The hypothesized path relationships between significant factors and entrepreneurial behavior have been found to be statistically significant. The top management of the companies in the IT industry have to focus and provide more importance to the entrepreneurship-institutional linkages which plays a key role in developing entrepreneurial behavior among the employees and in due course lead to innovative products and services and the over-all development of the organization.